2015
DOI: 10.1210/jc.2015-1444
|View full text |Cite
|
Sign up to set email alerts
|

Children With Morbid Obesity Benefit Equally as Children With Overweight and Obesity From an Ongoing Care Program

Abstract: Children with overweight, obesity, and morbid obesity benefit equally from an ongoing, outpatient, tailored lifestyle intervention, and demonstrate significant weight loss and improvement of cardiovascular risk parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 35 publications
1
90
1
Order By: Relevance
“…The findings from Rijks et al . also suggest a difference in BMI z‐score improvement between children and adolescents. Likewise, Danielsson et al .…”
Section: Influence Of Age and Gendermentioning
confidence: 97%
See 2 more Smart Citations
“…The findings from Rijks et al . also suggest a difference in BMI z‐score improvement between children and adolescents. Likewise, Danielsson et al .…”
Section: Influence Of Age and Gendermentioning
confidence: 97%
“…To summarize, existing evidence supports the implementation of family involvement into a multidisciplinary program as this may improve the chances of long‐term weight loss .…”
Section: Family Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to children with overweight or obesity, lifestyle approaches and standard behavioral interventions have been shown to be less effective; more intensive treatments are recommended to improve both obesity (e.g., BMI percentile) and health metrics (e.g., blood glucose) (Danielsson, Kowalski, Ekblom, & Marcus, 2012; Johnston et al, 2011). Traditionally, interventions for severe obesity have included intensive family-based treatment (sometimes as an inpatient) (Luca et al, 2015; Taylor, Peterson, Garland, & Hastings, 2016; van der Baan-Slootweg, Benninga, Beelen, et al, 2014), bariatric surgery (Nobili et al, 2015; Schmitt et al, 2016; Thakkar & Michalsky, 2015), medication (Boland, Harris, & Harris, 2015), and/or long-term treatment using a chronic care model (Rijks et al, 2015). Therefore, school-based interventions for children with severe obesity must be coupled with more intensive treatment to lead to clinically meaningful decreases in body measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a limited understanding of the long-term effects of multidisciplinary treatment programmes. The results of studies that examined an extended follow-up time have shown inconsistent outcomes regarding maintainable lifestyle changes leading to weight loss and health improvement, thus questioning the efficacy of present interventions [5,6]. In addition, evidence suggests rather to focus on health risk assessment, on health improvement, not just reduction in body size (or BMI corrected for age and sex), in particular in vulnerable target groups.…”
mentioning
confidence: 99%